International Public Sector Accounting Standards: the perception municipal accountants in Santa Catarina state have about implementing a cost accounting system - Fabrícia Silva da Rosa; Luana Caroline Silva; Sandro Vieira Soares (Contabilidad y Negocios: Revista del Departamento Académico de Ciencias Administrativas, 2015)
The objective of this article is to identify the perception municipal accountants in Santa Catarina State have about implementing a cost accounting system in public administration. This research was carried out due to the empha- sis on using a cost accounting system, which is part of International Public Sector Accounting Standards, so it is important to analyze compliance by municipalities. The methodology of this study shows descriptive objectives and procedures, as well as a qualitative and quantitative approach. A survey was conducted to accountants work- ing for the municipalities in the state of Santa Catarina. Totally, 97 respondents (32.88% out of the population of 295 municipalities). The analysis was done using descriptive statistics and correlation analysis. Results showed that municipal accountants have a positive perception, which means that they accept the importance of implementing a cost accounting system in public administration, but only one (01) municipal government implemented a cost accounting system and fourteen (14) are in the implementation process.